2020
DOI: 10.1242/jeb.231613
|View full text |Cite
|
Sign up to set email alerts
|

The impact of long-term reduced access to cleaner fish on health indicators of resident client fish

Abstract: In many mutualisms, benefits in the form of food are exchanged for services such as transport or protection. In the marine cleaning mutualism, a variety of “client” reef fishes offer “cleaner” fish Labroides dimidiatus access to food in the form of their ectoparasites, where parasite removal supposedly protects the clients. Yet, the health benefits individual clients obtain on the long-term from repeated ectoparasite removal remain relatively unknown. Here, we tested whether long-term reduced access to cleanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…We provide an explicit analysis that combines both cognitive performance and brain size as a function of body size in the cleaner fish Labroides dimidiatus (hereafter “cleaner”). Cleaners engage in iterative mutualistic interaction with a variety of coral reef fish (hereafter “client”) to remove their ectoparasites and dead tissue in exchange for food [Losey, 1979], a behaviour that is mutually beneficial for both cleaners [Grutter, 1999] and clients [Demairé et al, 2020; Ros et al, 2020; Clague et al, 2011]. Cleaner fish show a highly sophisticated strategic behaviour that includes reputation management [Bshary, and Grutter, 2002; Binning et al, 2017], social tool use [Bshary et al, 2002], reconciliation [Bshary, and Würth, 2001], and social competence [Triki et al, 2020a].…”
Section: Introductionmentioning
confidence: 99%
“…We provide an explicit analysis that combines both cognitive performance and brain size as a function of body size in the cleaner fish Labroides dimidiatus (hereafter “cleaner”). Cleaners engage in iterative mutualistic interaction with a variety of coral reef fish (hereafter “client”) to remove their ectoparasites and dead tissue in exchange for food [Losey, 1979], a behaviour that is mutually beneficial for both cleaners [Grutter, 1999] and clients [Demairé et al, 2020; Ros et al, 2020; Clague et al, 2011]. Cleaner fish show a highly sophisticated strategic behaviour that includes reputation management [Bshary, and Grutter, 2002; Binning et al, 2017], social tool use [Bshary et al, 2002], reconciliation [Bshary, and Würth, 2001], and social competence [Triki et al, 2020a].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Waldie et al (2011) found that two damselfish species were larger on control reefs compared to those from which L. dimidatus had been removed for 8.5 years. After 13 years of cleaner removal, body condition in four species of damselfish was lower on reefs without cleaners compared to those with cleaners (Ros et al, 2020). Thus, over the long term, parasite removal by cleaners may free up energy and resources (e.g.…”
Section: Signals Benefits and Costs In Cleaning Interactionsmentioning
confidence: 99%
“…Ros et al, 2011) that clients can then channel towards critical processes such as maintaining body condition (e.g. Ros et al, 2020) and growth (e.g. Waldie et al, 2011).…”
Section: Signals Benefits and Costs In Cleaning Interactionsmentioning
confidence: 99%
“…Thus, iterated cleaning visits help clients get rid of their current parasites, but it does not prevent reinfections (Grutter et al 2018(Grutter et al , 2019. Clients benefit from accessing cleaning services, like having improved body condition (Clague et al 2011;Waldie et al 2011;Ros et al 2020) and higher hematocrit levels (Demairé et al 2020). The study by Demairé et al…”
Section: Empirical Datamentioning
confidence: 99%